Metrological challenges for measurements of key climatological observables Part 2: oceanic salinity. (15th December 2015) - Pawlowicz, R; Feistel, R; McDougall, T J; Ridout, P; Seitz, S; Wolf, H
Abstract: Salinity is a key variable in the modelling and observation of ocean circulation and ocean-atmosphere fluxes of heat and water. In this paper, we examine the climatological relevance of ocean salinity, noting fundamental deficiencies in the definition of this key observable, and its lack of a secure foundation in the International System of Units, the SI. The metrological history of salinity is reviewed, problems with its current definitions and measurement practices are analysed, and options for future improvements are discussed in conjunction with the recent seawater standard TEOS-10.